Cerebral vasculitis due to Aspergillus spp. in immunocompromised patients: literature review. (September 2022) - Haddad, Elie; Fekkar, Arnaud; Bonnin, Sophie; Shor, Natalia; Seilhean, Danielle; Plu, Isabelle; Touitou, Valérie; Leblond, Véronique; Weiss, Nicolas; Demeret, Sophie; Pourcher, Valérie
Highlights: Cerebral invasive aspergillosis affecting large caliber vessels in immunocompromised patients is discussed. Diagnosis of invasive aspergillosis may be very challenging. Cerebral invasive aspergillosis may have atypical clinical presentation. Antifungal therapy is the mainstay of medical management. With proper follow-up, the prognosis of these patients would improve. Abstract: Objectives: Invasive aspergillosis is a threat for immunocompromised patients. We present a case series of aggressive cerebral vasculitis caused by Aspergillus spp. infection in immunocompromised patients. Methods: We present a retrospective case series of three autopsy-proven invasive cerebral aspergillosis with diffuse vasculitis affecting large caliber cerebral vessels. Results: Three patients were immunosuppressed: one on rituximab, one on corticosteroids, and one with a renal transplant. Two of these patients were diagnosed with cerebral aspergillosis on postmortem. Conclusion: Aspergillus cerebral vasculitis is a rare form of invasive aspergillosis that should be considered in an immunocompromised individual with suggestive lesions on imaging. It should be suspected as a possible cause of aseptic neutrophil meningitis.